2019
DOI: 10.26477/jbcd.v31i2.2618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Supplementation for Rabbits of Pomegranate seed Extract on Some Serum Biochemical Parameters in Relation to oral Inflammation, oxidative stress, and wound healing

Abstract: Background: Pomegranate (punicagranatum L, Punicaceae), is an edible fruit consumed around the world. The edible part of pomegranate is rich in compounds that possess antioxidant and anti-inflammatory activities. The aim of this study is to investigate the antioxidant; anti-inflammatory and gingival wound healing effects of Punicagrantum L. seed extract oral supplementation in rabbit. Methods and Methods: Forty five male rabbits were divided into 3 groups, base line (5 rabbits) left without buccal gingival wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These findings are in agreement with the results of the Florence et al (2017) study [21]. In another research on treatment by oral supplementation of pomegranate peel extract in a mandibular bone defect in a rabbit, on day 7 post-surgery, the level of calcium decreased [22]. A previous study has reported that the level of blood calcium increases following an increment in the dosage of the Arjuna Terminalia extract, and repair occurs more rapidly in the group with a higher dose of extract.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in agreement with the results of the Florence et al (2017) study [21]. In another research on treatment by oral supplementation of pomegranate peel extract in a mandibular bone defect in a rabbit, on day 7 post-surgery, the level of calcium decreased [22]. A previous study has reported that the level of blood calcium increases following an increment in the dosage of the Arjuna Terminalia extract, and repair occurs more rapidly in the group with a higher dose of extract.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have investigated the bone healing process using biochemical markers of the bone formation such as calcium, phosphorus, and alkaline phosphatase [6,[21][22][23][24]. High levels of calcium and phosphorus in the blood and extracellular fluids trigger the deposition of calcium phosphate crystals in the osteoid and make it harder [25].…”
Section: Discussionmentioning
confidence: 99%
“…Bw for 21 days [19]. Pomegranate seeds extract tablets were supplied to groups III and IV on day one following the administration of AFB1 at 100 mg/Kg [20].…”
Section: Experimental Protocolmentioning
confidence: 99%